Sistema de indicadores que fomenten el turismo sostenible en la Provincia de Manabí - Rodríguez Macías, Luis Fernando (2018)
The main objective of the research was to design a system of sustainable development indicators for the tourism sector in the province of Manabí, the same that is of a descriptive-exploratory type with a qualitative-quantitative approach; three specific objectives were set for the development of the research; The first objective was to diagnose the tourism sector, which was based on the delimitation and characterization of the province under study, continued by the analysis of tourism management, it was possible to obtain the relevant criteria by the actors involved through the matrix of involved and interviews directed to the main actors involved; based on that the SWOT matrix was developed identifying the problems of Manabí. The second objective is based fundamentally on the results of the bibliography review of the international organizations and pilot plans, generating a preliminary list, obtaining the relevant results for the decision making in the destination, and then elaborating a list of problems to correlate them with the indicators. The third objective was established in evaluating the indicators through the Delphi method, consisting of four areas of sustainability, 23 topics and 37 sustainability indicators, synthesized through a technical sheet for each indicator, which fulfill the functions of obtaining and interpreting and evaluating the information that they produce to carry out the decision-making and thus exercise the rectory in a sustainable manner within the planning and tourism management of Manabí.